Persepsi Pemuda terhadap Pekerjaan Sektor Perikanan Budidaya (Studi Kasus: Pemuda Desa Windu Kecamatan Karangbinangun Kabupaten Lamongan Jawa Timur) - Purnamasari, Ika; Moch Saad, Moch Saad; Laily, Dona Wahyuning (Universitas Galuh, 2024)
Currently, the reality shows that there has been a shift in interest in working from the fisheries sector to the non-fisheries sector. This is due to the loss of knowledge and skills of fishing village youth and a decline in perceptions regarding fisheries work. The aim of this research is to determine youth perceptions about jobs in the aquaculture sector and to determine the influence of youth perceptions on interest in employment in the aquaculture sector. The data analysis methods used are descriptive analysis and multiple linear regression analysis. The results of the research show that the youth's perception of work in the aquaculture sector as a whole is quite positive. The results of the F test show that the independent variables (income, social status, business risk, work comfort and family environment) together have a significant effect on youth interest in aquaculture sector work. Meanwhile, partially the youth perception variables that have a real influence on youth interest in aquaculture sector work are the income, business risk and work comfort variables. The variables of social status and family environment do not significantly influence young people's interest in aquaculture sector work